Photodynamic therapy: Truly a marriage between a drug and a light - Harveen Singh; Heena Khurana; Harshneet Singh; Manmohit Singh (Wolters Kluwer Medknow Publications, 2014)
Microbial biofilms in the oral cavity are involved in the etiology of various oral conditions, including caries, periodontal and endodontic diseases, oral malodor, denture stomatitis, candidiasis and dental implant failures. It is generally recognized that the growth of bacteria in biofilms imparts a substantial decrease in susceptibility to antimicrobial agents compared with cultures grown in suspension. It is therefore not surprising that bacteria growing in dental plaque, a naturally occurring biofilm, show increased resistance to antimicrobial agents. As result there is pronounced interest and keenness in the development of alternate antimicrobial concepts. Therefore, the application of alternative method to eradicate bacteria from periodontal pockets is desirable. One such approach is photodynamic therapy (PDT). The purpose of this review was to evaluate the effectiveness of PDT for periodontitis as an adjunct to non-surgical treatment of scaling and root planning. This review provides an overview of PDT with emphasis on its current status as an antimicrobial therapy to control oral bacteria. Finally, new frontiers of antimicrobial PDT research will be introduced, including targeting strategies that may open new opportunities for the maintenance of bacterial homeostasis in dental plaque, thereby providing the opportunity for more effective disease prevention and control. Thus, the available knowledge of PDT should encourage a more clinically oriented application of this technique.